Detection of Leishmania infantum amastigotes in neutrophil from peripheral blood in a naturally infected dog - Gilsan Aparecida de Oliveira; Vitória Aline Santos Sarmento; Ericka Wanessa da Silva Costa; Rômulo Pessoa-e-Silva; Rayana Carla Silva de Morais; Roberto Rômulo Ferreira; Ana Paula Sampaio Feitosa; Fábio André Brayner; Luiz Carlos Alves (Revista Brasileira de Parasitologia Veterinária, 2021)
Abstract Canine visceral leishmaniasis (CVL) is a zoonotic disease of high lethality caused by Leishmania infantum in the Americas. In the infected dog, the amastigotes are scarce in blood, especially in the late phase of the disease. This study aimed to report a rare case of L. infantum amastigotes found in neutrophils from peripheral blood of a naturally infected dog in terminal phase of CVL, also describing its clinical status before and after treatment with miltefosine 2%. The dog, which presented as polysymptomatic and with classical signs and symptoms of CVL was submitted to the following tests: Dual Path Platform (DPP) rapid test, ELISA and parasitological examination of peripheral blood. Hematological and biochemical parameters were obtained before and after treatment. All diagnostic tests were positive for CVL. The identification of L. infantum amastigotes inside neutrophils from peripheral blood was confirmed through microscopy, and the species was confirmed by molecular analysis. At the end of the treatment, peripheral parasitemia was not detected, and improvements were observed in clinical and laboratorial parameters. Finally, this atypical finding can be used as example to raise discussions about the real immunological role of neutrophils in late phases of CVL and its clinical/therapeutic implications.